Pregnancy Outcome Following Pelvic Infection - Miklos Toth; Anu Chaudhry; William J. Ledger; Steven S. Witkin (Hindawi Limited, 1993)
To determine whether a previous pelvic infection has an effect on the outcome of a subsequent pregnancy, we identified women with a diagnosis of pelvic inflammatory disease (PID), amnionitis, and postpartum or postabortal endometritis-salpingitis by a retrospective chart review of all patients admitted to the Department of Obstetrics and Gynecology at The New York Hospital-Cornell Medical Center between 1975 and 1977 and between 1985 and 1988. Antimicrobial regimens effective against Chlamydia trachomatis were initiated in 1985. Controls were randomly selected patients presenting during the same time period for routine examinations who had normal Pap smears and no infections. Both groups were comparable for age, race, gravity, and parity. Differences were evaluated by chi square analysis, using the Yates correction factor. We identified 183 women with a history of the above infections who subsequently conceived, and 82 controls. There were no differences in outcome between the two index groups. Term vaginal deliveries occurred in 14.2% of the women with a prior pelvic infection and in 56% of the controls (P < 0.001). Among the 97 women who had had PID, 21 (21.6%) had a spontaneous abortion in the subsequent pregnancy, as opposed to 6 (7.3%) of the controls (P = 0.013). In addition, eight of the women with PID (but no controls) went into preterm labor (P = 0.021). An increased incidence of preterm labor (P = 0.001) was also observed in women with a history of amnionitis. A history of endometritis was not associated with an increased prevalence of abnormal outcome in subsequent pregnancies. PID and amnionitis may adversely affect the outcome of subsequent pregnancies.